"Watipa Leza": A Critical Re-Engagement of Nsenga (African) Religious Values and Disability. (2nd April 2016) - Zulu, Edwin
Abstract: There are many misconceptions about disability in most African contexts. Most of these misconceptions are due to diverse views on disability. Consequently, these misconceptions have been a basis for practices that encourage discrimination against people living with disabilities. The thrust of this article is that, by re-engaging the African values on the view of humans and community, negative views on disability could be deconstructed, thereby creating a non discriminatory, non-exclusive and interactive community.